(untitled) (Global Journal of Management and Business Research, 2018)
Financial ratio analysis has been the ultimate tool for assessing the financial performance of organizations. However, given the increasing complexities in business operations in recent times, there is increasing shift to alternative methods that takes a multi-dimensional approach and combine several indicators to assess the financial performance of an organization. This study, therefore, aims at establishing Financial Performance Assessment Indices for evaluating banks performance in Ghana. Secondary data which spans over a 5-year period, covering 14 financial ratios on 24 registered banks in Ghana, was extracted from the annual Ghana Banking Survey reports. Analysing the data using descriptive statistics, ANOVA, and Principal Component Analysis technique, the study confirmed the existence of correlation among sets of financial ratios. The study also identified four basic Financial Performance Assessment Indices; Share of Industry Asset Index, Bank Profitability Index, Return on Bank Loan Index, and Liquidity Index. Among these indices, the Share of Industry Asset index and the Bank Profitability index constitute the most important for assessing the financial performance of banking institutions in Ghana.